Evaluation of Wonogiri Regency Regional Regulation Num-ber 3 of 2018 concerning the Implementation of Welfare in Wonogiri - Aziz Widhi Nugroho; Retno Eko Mardani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The implementation of social welfare is a directed, integrated, and sustainable effort carried out by the government, local governments, and the community in the form of social services to meet the basic needs of citizens. Wonogiri Regency has stipulated Regional Regulation Number 3 of 2018 concerning the Implementation of Social Welfare as a form of commitment to improve social welfare in its area. This study aims to analyze and evaluate the effectiveness of the implementation of these regulations using normative and empirical legal approaches, as well as qualitative descriptive analysis based on primary and secondary data. The results of the study show that although this Regional Regulation is an important instrument in the implementation of social welfare, it has not been able to answer all the dynamics and actual challenges. The channels, objectives, and benefits of the program have not been optimally accommodated, and there are weaknesses in the development of technical regulations that should be followed up through the Regent Regulation. With the age of seven years, this Regional Regulation is considered less relevant to current needs and needs to be updated to be able to accommodate social developments and ensure the effectiveness of the implementation of social welfare as a whole and sustainable in Wonogiri Regency.